Solar System Teaching Aids as Self-Practicum Through Youtube to Improve Students Learning Outcomes - Fatikhatun Nikmatus Sholihah; Muhammad Afiv Wahyudi (SCHOOLAR: Social and Literature Study in Education, 2022)
The aim of this study is to remind the results of cognitive learning of learners by making solar system props through youtube. This research used pre-experiment with pretest postest design. The research instruments used are questionnaires andtests. Research data analysis technique is to use quantitative analysis with the help of SPSS. The cognitive learning outcomes of learners increased from an average score of 57.67 to 85.33. This increase is due to the learner's understanding of the differences in characteristics and sizes between planets increased. Based on the results of the test t using SPSS, obtained Sign< 0.05 which is 0.000. It can then be stated that there is a significant difference between the pretest and postes values. In other words, there is an increase in student learning outcomes after the implementation of discovery learning through the manufacture of solar system props